Woman Trafficking dan Respon Gereja di Nusa Tenggara Timur - Ester Mariani Rihi Ga (Sekolah Tinggi Teologi Intheos Surakarta, 2022)
Abstract. This study was a critical study to the response of the Evangelical Christian Church in Timor (GMIT) towards women trafficking phenomenon in East Nusa Tenggara (NTT). The purpose of this study was to uncover the causes of women trafficking, as well to reveal the church's response to this phenomenon. This research was conducted by a qualitative method. In this study, it was revealed that the perception of women as the second sex in a patriarchal society is the main cause of women trafficking. The church also still pays more attention to spiritual services and even participates in perpetuating patriarchal culture so that it has not provided a maximum solution to the phenomenon of women trafficking.Abstrak. Studi ini merupakan kajian kritis terhadap sikap Gereja Masehi Injili di Timor (GMIT) terhadap fenomena perempuan yang marak terjadi di Nusa Tenggara Timur (NTT). Tujuan penelitian ini adalah untuk menguak penyebab terjadinya perdagangan perempuan dan mengungkap respon gereja menyikapi fenomena tersebut. Penelitian ini dilakukan dengan metode kualitatif. Dalam penelitian ini terkuak bahwa anggapan perempuan sebagai gender kedua dalam masyarakat patriarkhi menjadi penyebab utama terjadinya perdagangan perempuan. Gereja juga masih lebih banyak memberikan perhatian pada pelayanan rohani dan bahkan turut melanggengkan budaya patriarkhi sehingga belum memberikan solusi maksimal terhadap fenomena perdagangan perempuan.